Drawing Partnership on Paper: How do the Forms for Individual Educational Plans Frame Parent - Teacher Relationship? - Karila, Kirsti; Alasuutari, Maarit (International Journal about Parents in Education, 2023)
This article examines the Individual Educational Plan forms (hereafter IEP forms) used in planning for a child’s early childhood education and care (ECEC) in Finnish day care from the perspectives of social constructionism and discourse analysis. The National Curriculum Guidelines on Early Childhood Education and Care (Stakes, 2004 & 2005) require an Individual Educational Plan (IEP) to be drawn up for each child. Municipalities typically develop a local IEP form to be used in parent-teacher meetings at which the child’s IEP is discussed. The study examines how these IEP forms construct and frame parental and professional involvement in individual ECEC planning, and demonstrates that the positions of the parties in the IEP forms can be illustrated by two frames: an interview frame and a contract frame. These frames are considered in the present article in relation to the aims and principles articulated in the National Curriculum Guidelines on ECEC, which define the parent-teacher relationship as representing a partnership. The article also discusses the implications of the governing functions of the IEP forms from the perspective of the parent and the teacher.